Предмет: Математика, автор: dimok4110

Спростити вираз: *
Пожалуйста

Приложения:

Ответы

Автор ответа: alesyaperova
1

Ответ:

1) \frac{m + 4}{ {m}^{2} - 6m + 9 }  \times  \frac{m - 3}{ {m}^{2}  - 16}  =  \\  =  \frac{m + 4}{(m - 3) {}^{2} }  \times  \frac{m - 3}{(m - 4)(m + 4)}  =  \\  =  \frac{1}{(m - 3)(m - 4)}

2) \frac{1}{m - 4}  -  \frac{1}{(m - 3)(m - 4)}  \\  =  \frac{m - 3 - 1}{(m - 3)(m - 4)}  =  \\  =  \frac{m - 4}{(m - 3)(m - 4)}  =  \frac{1}{m -  3}

Пошаговое объяснение:

ответ:

 \frac{1}{m -3 }

Похожие вопросы
Предмет: Русский язык, автор: Леначкв